Monitoring tool wear process in turning machine using acoustic emission technique - Azlan, Mohd Saini (2010)
This project have been conducted in an attempt to monitor the changing of tool wear caused by increasing the cutting speed, through the variation of acoustic emission in turning process, under different feed and depth of cut. The signal-processing analysis was done on the raw signal, on the Acoustic Emission, signal filtered using a high bandpass and on the Acoustic Emission signal filtered using a smaller bandpass. The relationship among several parameters of Acoustic Emission such as zero crossing rate and standard deviation of Acoustic Emission was established. The material machined was mild steel and uncoated carbide cutting tool. The cutting force was also monitored. The results show that acoustic emission can be a good way to monitor on line the growth of tool wear in turning process and therefore can be useful for establishing the end of tool life in these operations. Based on the results obtained pointing out the best Acoustic Emission parameters to monitor tool wear, a set-up is proposed to reach to this goal of project.